On-surface synthesis of doubly-linked one-dimensional pentacene ladder polymers. Issue 97 (17th November 2020) - Biswas, Kalyan; Urgel, José I.; Sánchez-Grande, Ana; Edalatmanesh, Shayan; Santos, José; Cirera, Borja; Mutombo, Pingo; Lauwaet, Koen; Miranda, Rodolfo; Jelínek, Pavel; Martín, Nazario; Écija, David
Abstract : On-surface investigations of pentacene molecules functionalized with four dibromomethylene groups reveal, after an annealing step, the formation of π-conjugated ladder polymers doubly-linked by ethynylene bridges on a Au(111) surface. Abstract : On-surface synthesis has recently become an essential approach toward the formation of carbon-based nanostructures. Special emphasis is set on the synthesis of π-conjugated polymers taking into consideration their relevance and potential in organic electronics, optoelectronics and spintronics. Here, we report the on-surface synthesis of conjugated ladder polymers consisting of pentacene units doubly-linked via ethynylene-like bonds on the Au(111) surface under ultra-high vacuum conditions. To this aim, we have sublimed pentacene-like precursors equipped with four :CBr2 functional groups to steer the desired reaction upon annealing on the surface. The atomically precise structure of the obtained polymers has been unambiguously characterized via low-temperature scanning tunneling microscopy and non-contact atomic force microscopy. In addition, scanning tunneling spectroscopy complemented with density-functional theory calculations reveal the narrow bandgap of the polymer. Our results provide potential for the synthesis of π-conjugated polymers with prospects in functional carbon-based nanomaterials that exploit multiple connections between molecular backbones.